Survival of Xanthomonas campestris pv. Oryzae and its Control in Kuttanad - Mary C A (Department of plant Pathology, College of Agriculture, 1996)
The present investigation was taken up to understand the factors responsible for the recurrence of bacterial blight disease in a severe from only during the additional crop season in Kuttanad. The mode of survival of the pathogen during and in between the two major cropping seasons of Kuttanad region were also studied in detail. An extensive survey was also conducted among 115 farmers in 12 Krishibhavans of Kuttanad taluk for this purpose to collect specific informations on existing cultural practices, crop variety, nature and distribution of weed flora and self sown rice plants in and around rice fields and on wether data from June 1992 to March 1994. The efficacy of two different methods of spraying, prophylactic and curative using streptocycline, mixture of streptomycin and oxytetracycline in the proportion 1:9, Bactrinol – 100 cowdung extract on the control of bacterial blight disease was tested under field condition at Nedumudi in Kuttanad.